Systemic Drivers of Effective Crisis Communication: A Narrative Review Across Contexts - Hapsari, Galuh Kusuma; Ananda, Annisa Rizki (Indonesian Scientific Publication, 2024)
Organizational communication is pivotal in sustaining institutional resilience during crises, yet systematic evidence from Southeast Asia and Indonesia remains limited. This narrative review aims to synthesize recent empirical findings on internal and external communication strategies, with a focus on their effectiveness in fostering trust, engagement, and organizational reputation. Literature published between 2019 and 2024 was retrieved from Scopus, Google Scholar, and PubMed using Boolean search strings, and a total of XX eligible studies were included in the final synthesis. Findings indicate that internal strategies emphasizing transparency, emotional support, and digital connectivity enhance employee morale and cohesion, while external strategies rely on pre-crisis reputation, real-time messaging, and sensitivity to socio-political contexts. The growing use of social media and AI enables real-time sentiment analysis and tailored outreach, though ethical concerns and technological disparities between developed and developing countries remain significant barriers. This review reaffirms the Situational Crisis Communication Theory (SCCT), while proposing contextual adaptations that incorporate cultural diversity and technological complexities. Practically, the study highlights the urgency of systemic reforms, capacity building, and adaptive policies to strengthen organizational communication in Indonesia and the broader Southeast Asian region.